The philosophical problem of vagueness - Edgington, D (Cambridge University Press, 2001)
Think of the color spectrum, spread out before you. You can identify the different colors with ease. But if you are asked to indicate the point at which one color ends and the next begins, you are at a loss. "There is no such point", is a natural thought: one color just shades gradually into the next.